Ritual Bungung Salapang: Kajian Kepercayaan Masyarakat Desa Bontorappo Kecamatan Tarowang Kabupaten Jeneponto - Ummul Wahyunita; Andi Ima Kesuma; St. Junaeda (Rayhan Intermedia, 2022)
This study aims to determine the background so that there are still people who believe in Bungung Salapang. This study shows that there are still people who believe that because the people who visit feel reciprocal, they also feel that the place is not made as a place for idols but is made a place to ask God but through an intermediary from a well. In addition, the community still carries out the Bungung Salapang ritual because based on the personal experience of visitors who initially only accompanied family members, but were amazed at what happened to their family members after performing the ritual, which then also made them do the same thing.